Post a New Question

math

posted by .

-(4/3)^2+(4/3)^0+4/3-(-4/3)^2+|-(4/3)^2|

  • math -

    ( 4 / 3 ) ^ 2 = 16 / 9

    - ( 4 / 3 ) ^ 2 = - 16 / 9


    ( 4 / 3 ) ^ 0 = 1


    ( - 4 / 3 ) ^ 2 = 16 / 9

    - ( - 4 / 3 ) ^ 2 = 16 / 9


    ( 4 / 3 ) ^ 2 = 16 / 9

    - ( 4 / 3 ) ^ 2 = - 16 / 9

    abs ( - 16 / 9 ) = 16 / 9



    -( 4 / 3 ) ^ 2 + ( 4 / 3 ) ^ 0 + 4 / 3 -( -4 / 3 ) ^ 2 +abs ( - (4 / 3 ) ^ 2 ) =

    - 16 / 9 + 1 + 4 / 3 - 16 / 9 + 16 / 9 =

    - 16 / 9 + 1 + 4 / 3 =

    - 16 / 9 + 9 / 9 + 4 * 3 / ( 3 * 3 ) =


    - 16 / 9 + 9 / 9 + 12 / 9 = 5 / 9

  • math -

    Thank you

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question